EFISIENSI TEKNIS, PERTUMBUHAN TEKNOLOGI DAN TOTAL FAKTOR PRODUKTIVITAS PADA INDUSTRI MENENGAH DAN BESAR DI INDONESIA - Muhammad Fazri; Hermanto Siregar; Nunung Nuryartono (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2017)
Indonesia's economic growth this decade has good development. Not only growing but also more stable than before the reform era which is visible from the persistence of Indonesia at the level of positive growth during the economic crisis of 2008. Growth was good was followed by a change in the proportion of manufacturing industry in Indonesia which, if seen followed by a decrease in the production of some subsector indices industry. Total factor productivity (TFP) is one measure to look at other factors apart from the impact on production inputs such as technical efficiency and technological growth. In this study, in addition to trying to calculate TFP in some manufacturing industries subsector, in this study also wants to see the value of technical efficiency and the growth of the technology is a component of TFP calculations by the method of Stochastic Frontier Analysis (SFA). The results show that there is growing value of technical efficiency in some industries and most industries experienced relatively low growth of the technology. In the era before and after the crisis most of the industry has increased TFP growth but some industry decreased TFP growth. Keywords: SFA, Technical efficiency, Technological growth, TFP